A loud winter's nap - Hudson, Katy (Capstone Young Readers, a Capstone imprint, 2017)
Every year Tortoise sleeps through winter. He assumes he isn't missing much. Will Tortoise sleep through another winter, or will his friends convince him to stay awake and experience the frosty fun of winter?